Effect of biochar and silicon with different phosphorus levels on maize yield and soil chemical properties - Abu Bakar, Muhammad Wasil; Uddin, M. K.; Kasim, Susilawati; Zaibon, Syaharudin; Shamsuzzaman, S. M.; Haque, A. N.A. (Technoscience Publications, 2025)
Silicon fertilizer combined with biochar improved the utilization of phosphorus fertilization applications. The experiment was carried out with eight treatment combinations with varying proportions of rice husk biochar, silicon, and phosphorus in a completely randomized design with 75 days of growth in the greenhouse. To identify the optimum rate of phosphorus combined with rice husk biochar and Si for maximizing maize yield and soil chemical properties. This experiment showed that the application of biochar combined with silicon has the potential to reduce the amount of phosphorus fertilizer requirement. The application of 5 t ha-1 RHB + 100% Si + 25% TSP showed the highest pH compared to other treatments. While application of 2.5 t ha-1 RHB + 100% Si + 100% TSP showed the highest exchangeable K, Ca and Mg. Moreover, the application of 5 t ha-1 RHB + 100% Si + 100% TSP recorded the highest dry biomass compared to other treatments. Lastly, the application of 5 t ha-1 RHB + 100% Si + 50% TSP Showed the highest cob length(cm), cob weight(g), no of grain per cob, and grain yield (t.ha-1) compared to other treatments. The combined application of biochar and silicon, along with 50% phosphorus, is recommended for improving maize yield and soil health in greenhouse conditions.